Socialization of Healthy Gadget Use as an Effort to Promote Healthy Lifestyles for Elementary School Children in Parepare City - Muhammad Naufal Alfaridzi; Firman Husain (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student dedication to the community aimed at applying academic knowledge to real-life situations while strengthening the role of students as agents of social change. This activity was carried out in collaboration with SD Negeri 48 Parepare, with the goal of promoting healthy digital literacy among elementary school students through an interactive socialization program titled “Healthy Gadgets: Wise Use of Technology.” The theoretical foundation of this activity is based on the concepts of community education, child character development, and digital literacy, emphasizing the role of socialization in shaping positive behavior. The proposed hypothesis states that an interactive approach can effectively improve students’ understanding of healthy and responsible gadget use. The implementation methods included interactive lectures, group discussions, and quizzes involving 30 fifth-grade students, selected based on their high level of gadget usage, while understanding was evaluated through simple pre-test and post-test assessments. The measured outcomes included students’ comprehension of gadget benefits, potential negative impacts, and healthy usage strategies. The results showed a significant improvement in students’ understanding, with the average pre-test score of 58% increasing to 84% after the interactive session. Positive impacts were also observed in the students’ enthusiasm during discussions and their willingness to adopt healthier gadget habits. These findings confirm that the interactive method is effective in building awareness and transforming students’ mindsets regarding healthy digital literacy. In conclusion, the interactive socialization conducted through the KKN program successfully enhanced students’ understanding of wise and healthy gadget use and made a tangible contribution to empowering elementary school students to face the challenges of the digital era.